1996
DOI: 10.1099/00207713-46-2-526
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Legionellaceae Based on Small-Subunit Ribosomal DNA Sequences and Proposal of Legionella lytica comb. nov. for Legionella-Like Amoebal Pathogens

Abstract: The 16s rRNA-encoding gene sequences from strains of the family Legionellaceae, Sarcobium lyticum, and Coxiella burnetii were determined. Phylogenetic relationships revealed that all Legionella spp. were members of a coherent monophyletic family. The blue-white autofluorescent species formed a defined cluster bounded by Legionella bozemanii and Legionella tucsonensis. The strains of Legionella pneumophila subsp. pneumophila and Legionella pneumophila subsp. fraseri shared 99.2% sequence identity. A legionella-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
66
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 43 publications
1
66
0
4
Order By: Relevance
“…The causative agent of Legionnaires 0 disease, L. pneumophila, was first characterised in 1977 following an epidemic of acute pneumonia among veterans of the American Legion in Philadelphia [1,2] and since then, 47 species and more than 60 serogroups have been isolated [3][4][5][6][7]. The bacterium is a Gram-negative, aerobic, non-spore-forming, unencapsulated bacillus.…”
Section: Introductionmentioning
confidence: 99%
“…The causative agent of Legionnaires 0 disease, L. pneumophila, was first characterised in 1977 following an epidemic of acute pneumonia among veterans of the American Legion in Philadelphia [1,2] and since then, 47 species and more than 60 serogroups have been isolated [3][4][5][6][7]. The bacterium is a Gram-negative, aerobic, non-spore-forming, unencapsulated bacillus.…”
Section: Introductionmentioning
confidence: 99%
“…There is also serological evidence associating LLAPs with respiratory disease in humans (Rowbotham, 1993 ;Benson et al, 1995). The grouping together of members of the genus Legionella is based on phenotypic similarities and is supported by molecular techniques (Brenner et al, 1985 ; Brenner, 1986 ;Fry et al, 1991 ;Harrison & Saunders, 1994 ;Hookey, 1995 ;Benson et al, 1996 ;Hookey et al, 1996 ;Ratcliff et al, 1997Ratcliff et al, , 1998. There are few discriminatory phenotypic tests for the differentiation of Legionella species (Benson & Fields, 1998 ;Harrison & Saunders, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, tests were negative for b-lactamase and browning of tyrosine-supplemented agar. The results of biochemical tests such as gelatinase, hippurate, oxidase and b-lactamase activities indicated that these strains did not belong to any currently described Legionella species (Hookey et al, 1996). No autofluorescence was observed when colonies of the three isolates were exposed to UV light.…”
mentioning
confidence: 86%
“…At the time of writing, 47 species have been described (Euzéby, 1997;Lo Presti et al, 2001), including four Legionella-like amoebal pathogens (Hookey et al, 1996;Adeleke et al, 2001). Twenty-one species are pathogenic to humans (Winn, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation